2005
DOI: 10.1002/pssc.200461575
|View full text |Cite
|
Sign up to set email alerts
|

Uniform growth of GaN on AlN templated (111)Si substrate by HVPE

Abstract: Uniform growth of thick GaN was attempted on an AlN templated (111) silicon substrate by hydride vapor phase epitaxy(HVPE). The results were very sensitive to the thickness of the AlN layer as well as the growth temperature. If the AlN is thinner than 50 nm, the surface of the silicon substrate was partly melted during the HVPE growth. If the AlN was thicker than 50 nm, the melting of the silicon surface was drastically suppressed. Uniform growth without degradation of the Si substrate was achieved at 1000 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
(13 reference statements)
1
20
0
Order By: Relevance
“…The high-density crack network could be found in samples D, some melt-back etching patterns also appeared in this sample, as shown in Fig. 4(D) indicated by arrows.Melt-back etching patterns were mainly caused by the Ga[20].…”
mentioning
confidence: 99%
“…The high-density crack network could be found in samples D, some melt-back etching patterns also appeared in this sample, as shown in Fig. 4(D) indicated by arrows.Melt-back etching patterns were mainly caused by the Ga[20].…”
mentioning
confidence: 99%
“…It was shown that the AlN layer thicker than 200 nm is effective to prevent the melt-back-etching phenomenon. But, because of the large lattice mismatch between GaN, AlN and Si, if the thickness is more than 200 nm, cracking in the grown layer often takes place to limit the improvement [7]. An AlN/GaN multi-layer might improve the results as in the case of MOVPE [8].…”
Section: Introductionmentioning
confidence: 98%
“…In order to improve the crystalline quality, growth is undertaken at temperatures higher than 1000 1C. The HVPE growth of (0 0 0 1) GaN on (111) Si substrate was also demonstrated, where the authors pointed out the occurrence of the melt-back etching phenomena [7]. In order to suppress the reaction at the hetero-interface, insertion of an AlN intermediate layer was undertaken.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is initiated by the formation of a Ga-Si solution at the heterointerface and it is called 'melt back etching' [10]. This reaction is more probable at process temperature higher than 1000 ο C. Therefore, the suppression of the melt back etching has been the issue to get a thick GaN on Si substrate.…”
mentioning
confidence: 99%